Familial hyperamylasaemia. Issue 5 (May 1997) - Cuckow, P M; Foo, A Y; Jamal, A; Stringer, M D
Abstract : A six year old boy underwent extensive investigation for recurrent abdominal pain and was found to have a persistently raised serum amylase. Endoscopic retrograde cholangiopancreatography was normal and macroamylasaemia was excluded. Serum amylase concentrations were found to be raised in other family members spanning three generations, all of whom were asymptomatic. Clearance studies suggested no evidence of a renal tubular defect and serum lipase concentrations were normal. This is the first report of apparently familial hyperamylasaemia and the mode of inheritance is consistent with an autosomal dominant pattern.